2019
DOI: 10.1002/pen.25148
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of interfacial strength of HDPE overmolded with EPDM

Abstract: Multicomponent injection molding often combines a stiff thermoplastic material with a thermoplastic elastomer or thermoplastic vulcanite. Recently, for high‐demanding applications, a novel process has been developed to replace these thermoplastic elastomers or vulcanite with a thermoset rubber, for example, NBR or EPDM. One of the most important properties of a two component product is an adequate adhesion between both components. This paper describes a method, which combines experiments and numerical simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Six et al [12] developed a healing model towards the quantification of the interfacial strength using to define the strength between layers of thermoplastic composites (semi-crystalline high-density polyethylene (HDPE) and thermoset ethylene propylene diene monomer (EPDM)) by the investigation of the parameters of curing and interface temperatures. Experimental results were supported with numerical modeling, and successful plate production was achieved in this study.…”
Section: Multi-materials Injection Moldingmentioning
confidence: 99%
“…Six et al [12] developed a healing model towards the quantification of the interfacial strength using to define the strength between layers of thermoplastic composites (semi-crystalline high-density polyethylene (HDPE) and thermoset ethylene propylene diene monomer (EPDM)) by the investigation of the parameters of curing and interface temperatures. Experimental results were supported with numerical modeling, and successful plate production was achieved in this study.…”
Section: Multi-materials Injection Moldingmentioning
confidence: 99%
“…Simulations can be helpful in describing conditions in the interface during processing. A very interesting approach to the simulative description of adhesion and its dependence on general conditions is shown by Six et al 11 By considering the relationships between material strength, degree of crosslinking and interdiffusivity of the hard component (derived from DSC measurements), a model is described which can be used to estimate the bond strength between PE and HDPE with respect to process conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Fuentes et al [13] observed a reduction in static contact angles with increasing maleic anhydride (MA) content in molten maleic anhydride-grafted polypropylene (MAPP)/polypropylene (PP) blends which was explained by covalent bonding between the MA groups and the glass substrate. For the combination of a thermoset rubber solid and thermoplastic melt, literature on reactive wetting is currently, to the best of our knowledge, lacking despite its importance for twocomponent (2K) injection molding of thermoset rubber with thermoplastics [21][22][23].…”
Section: Introductionmentioning
confidence: 99%